Robot-assisted resection of gastric duplication cysts in a child: a detailed case report - Riccardo Rizzo; Gabriele Lisi; Nino Marino; Giuseppe Lauriti; Dacia Di Renzo; Pierluigi Lelli Chiesa (PAGEPress Publications, 2018)
Gastric duplication cysts (GDCs) represent 4-9% of alimentary tract duplications. Early diagnosis and surgical excision are essential to avoid morbidity or neoplastic degeneration. Roboticassisted excision of GDCs has never been described in childhood. We report an asymptomatic male patient with 2 gastric cystic masses at ultrasonography (US)-study (diameter 25mm and 8mm), increasing in size at follow-up. At 20 months of age, magnetic- resonance-imaging-scan confirmed 2 round gastric masses (44×35mm and 16×12mm, respectively). Two months later, an elective robotic-assisted excision of GDCs was completed without complications. The patient was discharged at day 6 after procedure. Histology confirmed the diagnosis of GDCs. At a 2-year follow- up, US-study did not evidence any issue. In this first reported case of robotic-assisted cystectomy for CGD in childhood, the procedure seems safe, effective, and feasible. This approach improves the movements of the surgical instruments with better 3- D visualization in comparison with the laparoscopic approach.